2010
DOI: 10.1002/etc.279
|View full text |Cite
|
Sign up to set email alerts
|

Complex contaminant exposure in cetaceans: A comparative E‐Screen analysis of bottlenose dolphin blubber and mixtures of four persistent organic pollutants

Abstract: Cetaceans are federally protected species that are prone to accumulate complex mixtures of persistent organic pollutants (POPs), which individually may exert estrogenic or antiestrogenic effects. In the present study it was assessed whether contaminant mixtures harbored by cetaceans are estrogenic or antiestrogenic using a comparative approach. Interactions of antiestrogenic and estrogenic compounds were first investigated with the E-Screen assay using a mixture of four POPs (dichlorodiphenyldichloroethylene [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…() and Yordy et al . (); briefly, MCF‐7 BOS cells (passages 71–93) reached ~80% confluence prior to experimentation. Cells were washed with experimental media (DMEM without phenol red, 5% CD‐FBS and 1% PSA), trypsinized and seeded into the inner 40 wells of 96‐well plates to a volume of 200 µl (10 4 cells per well) and allowed to attach for 24 h. The outer peripheral wells were not used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Yordy et al . (); briefly, MCF‐7 BOS cells (passages 71–93) reached ~80% confluence prior to experimentation. Cells were washed with experimental media (DMEM without phenol red, 5% CD‐FBS and 1% PSA), trypsinized and seeded into the inner 40 wells of 96‐well plates to a volume of 200 µl (10 4 cells per well) and allowed to attach for 24 h. The outer peripheral wells were not used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Antiestrogenicity is assessed with this assay by inducing the maximal proliferation of MCF-7 BOS cells with E 2 and measuring the reduction in proliferation that occurs as a result of co-exposure with the test compound. This method was previously described by Soto et al (1995) and Yordy et al (2010); briefly, MCF-7 BOS cells (passages 71-93) reached~80% confluence prior to experimentation. Cells were washed with experimental media (DMEM without phenol red, 5% CD-FBS and 1% PSA), trypsinized and seeded into the inner 40 wells of 96-well plates to a volume of 200 ml (10 4 cells per well) and allowed to attach for 24 h. The outer peripheral wells were not used in the experiment.…”
Section: E-screen Bioassaymentioning
confidence: 99%
“…In recent years, cocktail mixtures of chemicals and environmental pollutants have received growing attention. Evidence has shown that exposure to single compounds that do not induce an adverse effect can have negative synergistic and additive effects in organisms when exposure occurs as part of a mixture [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these studies, an additional step forward in in vitro studies has been the development of biosensor systems, which use engineered cells (i.e. bioassays) to be applied to marine mammals and concepts like 'effect-driven approach' (EDA), 'adverse outcome pathway' (AOP) and 'toxicity pathway' (Yordy et al 2010;Burgess et al 2013;Jin et al 2013Jin et al , 2015Simon et al 2013). These developments allow to screen marine mammal tissue samples with respect to specific endpoints and, depending on the study design, can be used as an initial step to explore the influence of contaminant mixtures.…”
Section: In Vitro Researchmentioning
confidence: 99%